Case report: Scleromyxedema associated with a monoclonal gammapathy: Successful treatment with intravenous immunoglobulins - Wang, Shang-shang; Chen, Qin-yi; Xiang, Lei-hong (Frontiers in Immunology, 2023)
Scleromyxedema is a rare idiopathic fibromucinous disorder characterized by a generalized papular and sclerodermoid cutaneous eruption. Patients often have praraproteinemia and extracutaneous, even lethal, manifestations. Yet the prognostic and therapeutic features are poorly documented. High-dose intravenous immunoglobulin has been suggested as the first-line treatment used either alone or in conjunction with systemic steroids and/or thalidomide. Herein we reported a 45-year-old woman diagnosed as scleromyxedema with paraproteinemia initially failed to respond to systemic steroids, retinoid and thalidomide but achieved great improvement after intravenous immunoglobulins treatment.